2014
DOI: 10.1002/jctb.4499
|View full text |Cite
|
Sign up to set email alerts
|

Study on active coke‐based adsorbents for SO2 removal in flue gas

Abstract: BACKGROUND: A series of active coke-based adsorbents from different sources, treated with acid-base, modified by metal compounds and calcined at different temperatures were investigated for SO 2 removal from flue gas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…In our previous researches, alkali (especially KOH) has shown a good enhancement effect on the adsorption of adsorbent and the catalytic oxidation of catalyst . Therefore, the CSAC adsorbent was first pretreated by KOH with different mass fraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous researches, alkali (especially KOH) has shown a good enhancement effect on the adsorption of adsorbent and the catalytic oxidation of catalyst . Therefore, the CSAC adsorbent was first pretreated by KOH with different mass fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al found that the K element has a strong interaction effect on the surface of γ-AL 2 O 3 that being conducive to the NO x adsorption. In our previous research, we found that alkali species (especially KOH) being an additional active component metal had a good enhancement effect on the adsorption of adsorbent. Nikolov et al studied the adsorption of NO on transition metal Cu modified activated carbon under the condition of room temperature and found that the addition of Cu significantly improved the adsorption of NO on activated carbon.…”
Section: Introductionmentioning
confidence: 94%
“…The surface functional groups of activated coke can be enriched by HNO 3 treatment, which favors the adsorption of SO 2 . The relative content of oxygen‐containing functional group is increased by HNO 3 , which can play a favorable role in their improved SO 2 adsorption abilities …”
Section: Resultsmentioning
confidence: 99%
“…14 The relative content of oxygen-containing functional group is increased by HNO 3 , which can play a favorable role in their improved SO 2 adsorption abilities. 15 In summary, NAC-800 was selected for adsorption-thermal regeneration cycling to explore its thermal regeneration performance. The coke after desulfurization was denoted as NAC-800-S.…”
Section: Comparison Of the Desulfurization Performance Of The Preparementioning
confidence: 99%
“…As a result, a large number of polluting gases are released, leading to deterioration of air quality and endangering people’s health. 9 Therefore, it is particularly important to find an efficient adsorbent for polluting gases. Activated coke is a material with a developed pore structure, strong selective adsorption capacity, large specific surface area, and easy regeneration performance.…”
Section: Introductionmentioning
confidence: 99%